Discovery of 3,5-Dimethyl-4-Sulfonyl‑1H‑Pyrrole-Based Myeloid Cell Leukemia 1 Inhibitors with High Affinity, Selectivity, and Oral Bioavailability - Zhu, Peng-Ju; Yu, Ze-Zhou; Lv, Yi-Fei; Zhao, Jing-Long; Tong, Yuan-Yuan; You, Qi-Dong; Jiang, Zheng-Yu (Journal of medicinal chemistry, 2021)
Myeloid cell leukemia 1 (Mcl-1) protein is a key negative regulator of apoptosis, and developing Mcl-1 inhibitors has been an attractive strategy for cancer therapy. Herein, we describe the rational design, synthesis, and structure–activity relationship study of 3,5-dimethyl-4-sulfonyl-1H-pyrrole-based compounds as Mcl-1 inhibitors. Stepwise optimizations of hit compound 11 with primary Mcl-1 inhibition (52%@30 μM) led to the discovery of the most potent compound 40 with high affinity (K d = 0.23 nM) and superior selectivity over other Bcl-2 family proteins (>40,000 folds). Mechanistic studies revealed that 40 could activate the apoptosis signal pathway in an Mcl-1-dependent manner. 40 exhibited favorable physicochemical properties and pharmacokinetic profiles (F% = 41.3%). Furthermore, oral administration of 40 was well tolerated to effectively inhibit tumor growth (T/C = 37.3%) in MV4-11 xenograft models. Collectively, these findings implicate that compound 40 is a promising antitumor agent that deserves further preclinical evaluations.